Outcomes and Prognostic Factors of Posttraumatic Endophthalmitis: A Three-Year Retrospective Study - Jian Ma; Yinhui Yu; Yueyang Zhong; Xing Mao; Xiaoyun Fang (Journal of Ophthalmology)
Purpose. To describe the clinical features, management, and outcomes of patients with posttraumatic endophthalmitis (PTE) and to determine risk factors for poor visual prognosis. Methods. We retrospectively reviewed the medical records of 42 consecutive patients presenting with PTE who were treated at our institution between 2017 and 2019. Each patient’s data, including demographic characteristics, ocular injury details, surgical records, patient outcomes, and laboratory results, were collected and analyzed. Multivariate analysis was conducted to determine the factors associated with poor visual outcomes. Results. In our series, male (n = 36, 85.7%) and patients below 60 years of age (20–40 years, 23.8%; 40–60 years, 57.14%) comprised most of the total cohort. On presentation, 39 (92.8%) of the 42 PTE patients presented best-corrected visual acuity (BCVA) worse than counting fingers. Pars plana vitrectomy (PPV) was performed in all the patients. 59.5% (n = 25) of the patients’ BCVA improved after surgery and 33.3% (n = 14) achieved BCVA of 20/200 or better. The rate of evisceration was 7.1% (n = 3). Of the 42 specimens, the culture was positive in 10 (23.8%) eyes. By univariate analysis, factors including sex, occupation, systemic disease, source of trauma, lens injury, silicone oil tamponade, usage of intravitreal antibiotics, BCVA at presentation, and culture positive for any organism did not affect the final visual outcome. The features associated with poor BCVA (grouped as < 20/200 and ≥ 20/200) included older age (P=0.035), corneal-sclera wound (versus sclera wound) (P=0.047), retained intraocular foreign bodies (IOFBs) (P=0.006), treatment > 3 days (versus < 1 day) (P=0.033), and more times of surgeries (P=0.033). Conclusions. PTE is a severe complication of penetrating globe injuries associated with irreversible visual loss. Our results highlighted the importance of conducting early therapeutic PPV and IOFB removal to achieve better visual outcomes.